Integrative assessment of fish diversity in abalone raft culture areas of the Pingtan Sea, China, based on traditional fishing and eDNA metabarcoding - Chao Ma; Tongjin Wu; Yong Liu; Chunyan Xu; Zhidong Zhuang; Sunzhong Ye; Jiandi Cai (Frontiers in Marine Science, 2026)
As offshore aquaculture expands globally, understanding how farming facilities integrate into and influence marine ecosystems is critical. This study evaluated the ecosystem functions of abalone raft culture in the Pingtan sea area, China, by employing an integrative framework that combined traditional sampling (gillnets and pots) with environmental DNA (eDNA) metabarcoding. Surveys were conducted from March to August 2024 to compare fish diversity and community characteristics between a raft culture area (RA) and a control area (CA). Traditional surveys identified 35 fish species in the RA, significantly higher than the 27 species found in the CA. The dominant species in the RA were identified as Sebastiscus marmoratus and Siganus fuscescens. In the RA, both the Margalef richness (2.326) and Shannon-Wiener diversity (1.853) indices were significantly higher than those in the CA ( P< 0.05), while the catch per unit effort (CPUE) for gillnets and pots increased by 25.7% and 33.0%, respectively. In parallel, eDNA metabarcoding detected 68 fish species across 12 orders and 41 families, successfully identifying key pelagic species such as Sardinella aurita and Clupanodon punctatus that were frequently missed by traditional gear. Alpha diversity analysis confirmed a significantly higher diversity level in the RA, and Principal Coordinate Analysis (PCoA) revealed a profound separation in community structure between the two habitats ( P < 0.0001). These results demonstrate that abalone raft culture facilities significantly enhance fish diversity (as shown by eDNA and traditional surveys) and resource abundance (as indicated by higher CPUE in traditional surveys) by increasing habitat heterogeneity through physical structures and restructuring food webs via nutrient enrichment. These findings suggest that these facilities function as “de facto” artificial reefs, providing a scientific basis for the “aquaculture-ranching” integration model and offering a standardized monitoring paradigm for the ecological management of coastal aquaculture zones globally.